Desenvolvimento de modelo hidrodinâmico do fluxo de óleo em um relé de proteção acoplado a um transformador de potência. - Lins, Ivan Xavier (2021)
The present work aims to propose a hydrodynamic study of a gas relay using the computational fluid dynamics tool, in order to predict the speed, temperature variation and oil pressure profiles, based on their physical properties, the expansion coefficient volume, and operating conditions, in order to obtain more accurate and reliable information regarding the volume of oil, inside the system. The proposed methodology will be based on three stages: preprocessing (development of a computational mesh, based on real three-dimensional geometry), processing (definition of boundary conditions and choice and resolution of hydrodynamic models in a FlowSimulation simulation environment) and post-processing (obtaining speed profiles, fin tilt, temperature and system pressure variation). The results show the upward flow, the fluid speed, there are significant temperature rises (above 60ºC and may be associated with transformer failures), including the behavior of the fluid dynamic flow and the pressure drop inside the system. Finally, an experimental study was carried out in order to validate the items simulated above. Through this study it was possible to observe the dynamic fluid behavior of the insulating oil in different failure situations, facilitating the understanding of the system. Being an important tool for the evaluation of the protection relay.